2013
DOI: 10.1002/ar.22685
|View full text |Cite
|
Sign up to set email alerts
|

Plasticity in the Cerebellum and Primary Somatosensory Cortex Relating to Habitual and Continuous Slender Branch Climbing in Laboratory Mice (Mus musculus)

Abstract: The origin of the mammalian order Primates is nested within a Euarchontan ancestry that was probably exploiting the fine branch arboreal niche in a facultative way. A putative transition into this habitat may have begun with a more generalized small-bodied mammal that lacked climbing specializations for grasping hands and feet. Here, we investigate whether mice exhibit central nervous system (CNS) plasticity associated with learning to grasp/climb proficiently. House mice were used to study phenotypic plastici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 94 publications
(111 reference statements)
0
7
0
Order By: Relevance
“…Previous work by Byron and colleagues using a similar mouse model of fine‐branch arboreal climbing demonstrated considerable skeletal adaptation over the same time course (Byron et al, ). Additionally, the Byron laboratory demonstrated significant central nervous system plasticity in their climbing mice, as the granular cell layers of cerebellar lobules responsible for coordinating muscle function of the tail are thicker, suggesting more muscle coordination (Byron et al, ). We expected to see adaptation of the hind limb skeletal musculature in the present study.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous work by Byron and colleagues using a similar mouse model of fine‐branch arboreal climbing demonstrated considerable skeletal adaptation over the same time course (Byron et al, ). Additionally, the Byron laboratory demonstrated significant central nervous system plasticity in their climbing mice, as the granular cell layers of cerebellar lobules responsible for coordinating muscle function of the tail are thicker, suggesting more muscle coordination (Byron et al, ). We expected to see adaptation of the hind limb skeletal musculature in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…Animals were raised in one of two custom enclosures: an experimental enclosure and a control enclosure. The experimental enclosure is a 2 ft 3 Plexiglas box traversed by multiple 2.25 mm diameter steel wires that create a three-dimensional climbing substrate approximating a fine branch arboreal niche (Byron et al, 2009(Byron et al, , 2011(Byron et al, , 2013. Wires are oriented either horizontal to the bottom of the enclosure or at 458 relative to horizontal.…”
Section: Custom Housing Enclosuresmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been shown that standard laboratory rodents as well as the European Red Squirrel locomote on slender substrates with adaptive behaviors that promote stability (Schmidt and Fischer, ). Recently, Byron et al () also promoted the use of a mouse model system that simulates a fine‐branch arboreal habitat. This is because pedal (specifically hallucal) prehension along with tail coordination are observed to help counteract the body's tendency to pitch and roll mediolaterally on narrow substrates (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…). The development of this skill for fine branch arboreality is evident at a cerebral and cerebellar somatotopic level (Byron et al, ). The habitual use of hallucal grasping commits the mouse to foot postures that place the substrate between the first and second digits.…”
Section: Introductionmentioning
confidence: 99%